A distinct, sequence-induced conformation is required for recognition of the constitutive decay element RNA by Roquin - Codutti, Luca; Leppek, Kathrin; Zálešák, Jan; Windeisen, Volker; Masiewicz, Pawel; Stoecklin, Georg; Carlomagno, Teresa (Structure, 2015)
The constitutive decay element (CDE) of tumor necrosis factor α (TNF-α) mRNA (Tnf) represents the prototype of a class of RNA motifs that mediate rapid degradation of mRNAs encoding regulators of the immune response and development. CDE-type RNAs are hairpin structures featuring a tri-nucleotide loop. The protein Roquin recognizes CDE-type stem loops and recruits the Ccr4-Caf1-Not deadenylase complex to the mRNA, thereby inducing its decay. Stem recognition does not involve nucleotide bases; however, there is a strong stem sequence requirement for functional CDEs. Here, we present the solution structures of the natural Tnf CDE and of a CDE mutant with impaired Roquin binding. We find that the two CDEs adopt unique and distinct structures in both the loop and the stem, which explains the ability of Roquin to recognize stem loops in a sequence-specific manner. Our findings result in a relaxed consensus motif for prediction of new CDE stem loops.
Gesehen am 02.12.2020